Dabigatran for stroke prevention in atrial fibrillation - Hohnloser, S. H.; Diener, H.-C. (Hämostaseologie, 2012)
Dabigatran is a novel direct thrombin inhibitor that has recently been approved for primary and secondary stroke prevention and prevention of systemic embolism in patients with atrial fibrillation. In the pivotal RE-LY study, dabigatran 110 mg BID was demonstrated to be associated with a stroke rate similar to that observed with warfarin (INR target 2.0 to 3.0), but with a lower rate of major haemorrhage. Dabigatran administered at a dose of 150 mg BID was significantly more effective in stroke prevention than warfarin and showed a similar rate of major hemorrhages. Of note, both dosages resulted in an approximately 60–70% relative risk reduction of haemorrhagic stroke. The dosage of 110 mg BID should be preferably used in patients aged 75–80 years or older as the rate of extracranial bleeding events tends to increase with dabigatran 150 mg BID above this age limit. In RE-LY, myocardial infarcts occurred at a very low incidence. There were numerically more myocardial infarcts in dabigatran-treated patients than in warfarin patients; however, other myocardial ischaemic events were similar in the three treatment arms.
Keywords: Atrial fibrillation; anticoagulation; stroke; dabigatran; warfarin